Political economy of the oil industry in the Sudan. Problem or resource in development - Lado, Cleophas (ERDKUNDE, 2002)
Sudan, the largest country in Africa, has endured the longest civil war on the continent after forty years of intermittent civil war. The Sudanese people have witnessed transitions including three parliamentary democracies and three periods of military rule. More than two million people have died in the past 16 years of civil war, and twice as many have been displaced, making it one of the greatest humanitarian disasters but one of the least reported. The civil war was claimed more lives than the wars in Bosnia, Kosovo, Chechnya and Somalia altogether. The specific focus of this paper is on the oil industry in Sudan - whether it is a problem or resource on development and the impact it has on the civil war. This study follows the inauguration of the Sudan’s 1600 km Greater Nile Petroleum Oil Corporation (GNPOC) pipeline, the longest in Africa, which has rejuvenated oil operations and heightened expectations of oil revenues flowing to the Government of Sudan (GOS). In order to put the current civil war in context, this article provides a background to the conflict. The importance of oil within the context of the Sudanese economy will be addressed, and the impact of ongoing oil exploration and production examined. The relationship between the major partners in the Sudan’s oil consortium and the GOS is of particular interest, as well as their role and stake in the industry. A key part of the paper examines the extent to which the GOS has attempted to control and protect oil operations by implementing strategies of divide and rule and fomenting conflict between ethnic groups. The humanitarian impact of such actions is devastating to the local populations and is outlined, including recommendations for serious engagement of all oil stakeholders and warring parties to peace talks to achieve a lasting solution to Sudan’s problem. Consequently, oil as a mineral wealth will be fully tapped for the socio-economic development of all the Sudanese people.